Refleksi Efektivitas Penerapan Coretax dalam Sistem Perpajakan Indonesia - Ahmad Baihaqi; Liris Kristina (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
Digital transformation in tax administration has become a strategic step to improve the effectiveness of tax management and taxpayer compliance. The Indonesian government has developed the Core Tax Administration System (Coretax) as an integrated core system aimed at strengthening national tax governance through data integration and improved administrative efficiency. The implementation of this system is expected to support the modernization of tax administration and enhance the quality of services provided to taxpayers. However, the effectiveness of Coretax implementation still requires comprehensive study to understand the challenges and implications in the practice of tax administration in Indonesia. This study employs a qualitative approach with a descriptive-analytical design. Data were collected through in-depth interviews with tax officials, tax practitioners, and taxpayers, as well as documentation studies of regulations and policy reports related to Coretax. Data analysis was conducted using thematic analysis to identify patterns and challenges in system implementation. The results show that Coretax contributes to data integration, administrative efficiency, and the strengthening of tax governance. However, its implementation still faces challenges related to infrastructure readiness, human resource capacity, and the level of taxpayer trust.